Densification in height and real estate market in the city of Lima (Peru) 2007-2017 - Calderón Cockburn, Julio (2022)
The article reviews the process of residential densification in the city of Lima between 2007 and 2017. It proceeds to classify the city of Lima in 6 areas: Lima Top, Lima central middle class, Lima Popular Worker, Lima North, Lima South and Lima East. The methodology defines the typology and reviews some population and housing indicators provided by the 2007 and 2017 population and housing censuses. Among his conclusions he confirms that the densification of housing is proven in the city of Lima, especially in its central area, reversing the trend towards depopulation observed towards the end of the 20th century. Densification in height is higher in Lima Top and Lima central middle class, and much lower in the rest of the city. This situation is due to the profitability of private real estate investment and the role of the State supporting it through flexibility in rules and subsidies.